Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1056/nejmc2021225
|View full text |Cite
|
Sign up to set email alerts
|

Retraction: Cardiovascular Disease, Drug Therapy, and Mortality in Covid-19. N Engl J Med. DOI: 10.1056/NEJMoa2007621.

Abstract: To the Editor: Because all the authors were not granted access to the raw data and the raw data could not be made available to a third-party auditor, we are unable to validate the primary data sources underlying our article, "Cardiovascular Disease, Drug Therapy, and Mortality in Covid-19." 1 We therefore request that the article be retracted. We apologize to the editors and to readers of the Journal for the difficulties that this has caused.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
90
1
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 412 publications
(98 citation statements)
references
References 1 publication
1
90
1
6
Order By: Relevance
“…The appropriate scoping of methods for real-world data studies is critical for the use of these valuable, emerging data sets. We have just witnessed the retraction of two data-driven COVID-19 studies from two of the most prominent clinical journals because of uncertainty about the provenance and quality of the data 4,5 . But the issue goes far beyond these two papers, as data provenance and analytical approaches are often not appropriately detailed in the methods of scientific publications.…”
mentioning
confidence: 99%
“…The appropriate scoping of methods for real-world data studies is critical for the use of these valuable, emerging data sets. We have just witnessed the retraction of two data-driven COVID-19 studies from two of the most prominent clinical journals because of uncertainty about the provenance and quality of the data 4,5 . But the issue goes far beyond these two papers, as data provenance and analytical approaches are often not appropriately detailed in the methods of scientific publications.…”
mentioning
confidence: 99%
“…Recently, two worldrenowned medical journals, The New England Journal of Medicine and The Lancet retracted two high-profile papers on treatments in patients with COVID-19. 31,32 One of the studies reported the results of clinical trials of two antimalarial drugs used for treatment of COVID-19 (chloroquine and hydroxychloroquine). 32 This retracted study claimed that these drugs were not associated with improved outcomes and were, in fact, associated with higher mortality in patients.…”
Section: Role Of Journals During a Public Health Crisismentioning
confidence: 99%
“…Two papers have been recently published in two of the most prestigious medical journals only to be retracted a few weeks later. The first onepublished on The New England Journal of Medicine (NEJM) on 1 May 2020-addressed the lack of harmful effects of ACE inhibitors and angiotensin receptor blockers in patients with COVID-19 4 ; the other-published on Lancet on 22 May 2020focused on the potential risks of using hydroxychloroquine (HCQ) or chloroquine as COVID-19 treatment. 5 These two papers share three authors (Professor Mandeep R Mehra, Dr Sepan S Desai and Dr Amit N Patel) 4 5 and also the source of the data analysed: Surgisphere, a data analytics company founded by Dr Desai in 2007.…”
Section: A Brief Introduction To Recent Events: the Surgisphere Scandalmentioning
confidence: 99%